Temporal trend and attributable risk factors of ischemic stroke burden in China, 1990–2021 - Zhengqi Lian; Yikun Gao; Jiali Xiong; Yang Shen; Xiaoxing Xiong; Lijuan Gu (BMC Neurology)
Abstract Background Ischemic stroke (IS) is the third leading cause of death and disability in China. The Global Burden of Disease (GBD) 2021 study provides the data on IS from 1990 to 2021. This study firstly analyzed the disease burden and risk factors for IS in China from 1990 to 2021, with a special focus on the epidemiological changes following the COVID-19 outbreak. Methods Based on GBD 2021 data, this study conducted a secondary analysis of the incidence, prevalence, mortality, disability-adjusted life years (DALYs), years of life lost (YLLs), and years lived with disability (YLDs) and attributable risk factors of IS in China from 1990 to 2021. Trends in IS were assessed by estimated annual percentage change (EAPC). All analyses were stratified by sex and age. Results IS incidence rose from 0.76 million in 1990 to 2.77 million in 2021 (EAPC: 4.21, 95% CI: 3.98–4.44). The prevalence increased from 6.58 million in 1990 to 20.80 million in 2021 (EAPC: 3.85, 95% CI: 3.62–4.08). The rates and age-standardized rates (ASRs) for these metrics increased from 1990 to 2021, with a sharp increase in 2020–2021. Although the number of deaths and DALYs rose to 0.28 million and to 5.01 million in 2021 respectively, the ASRs decreased from 1990 to 2021. The disease burden of IS is generally higher in males than in females at all ages. The IS burden were expected to continue growing from 2021 to 2030. In 2021, the top 3 risk factors for IS DALYs were High systolic blood pressure, Ambient particulate matter pollution, and High LDL cholesterol. Conclusions The disease burden of IS in China has notably increased over the past three decades, with significant differences in sex and age groups. The COVID-19 pandemic has changed the epidemiology of IS. China needs to take appropriate prevention and treatment measures for key populations, and pay attention to changes in IS management in the post-epidemic era.